Is flood defense changing in nature? Shifts in the flood defense strategy in six European countries - Mathilde Gralepois; Corinne Larrue; Mark Wiering; Ann Crabbé; Sue Tapsell; Hannelore Mees; Kristina Ek; Malgorzata Szwed (Ecology and Society, 2016)
In many countries, flood defense has historically formed the core of flood risk management but this strategy is now evolving with the changing approach to risk management. This paper focuses on the neglected analysis of institutional changes within the flood defense strategies formulated and implemented in six European countries (Belgium, England, France, the Netherlands, Poland, and Sweden). The evolutions within the defense strategy over the last 30 years have been analyzed with the help of three mainstream institutional theories: a policy dynamics-oriented framework, a structure-oriented institutional theory on path dependency, and a policy actors-oriented analysis called the advocacy coalitions framework. We characterize the stability and evolution of the trends that affect the defense strategy in the six countries through four dimensions of a policy arrangement approach: actors, rules, resources, and discourses. We ask whether the strategy itself is changing radically, i.e., toward a discontinuous situation, and whether the processes of change are more incremental or radical. Our findings indicate that in the European countries studied, the position of defense strategy is continuous, as the classical role of flood defense remains dominant. With changing approaches to risk, integrated risk management, climate change, urban growth, participation in governance, and socioeconomic challenges, the flood defense strategy is increasingly under pressure to change. However, these changes can be defined as part of an adaptation of the defense strategy rather than as a real change in the nature of flood risk management.